Classroom Assessment Investigations - Wilson, Robert J. (Alberta Journal of Educational Research, 1999)
Although much discussion of approaches to research concentrates on the differences between qualitative and quantitative models, some thought has been given to using both in single studies, mostly in program evaluation. One way out of the dilemma would be to adopt a non-foundationalist stance where the argument, no matter how constructed, would be subjected to debate and analysis by competent, interested spectators. This is the position taken by the authors as they each report on their analysis of data emanating from a single study, which explored preservice teachers' behaviors and perceptions as they assessed the work of an imaginary student named Chris. Finally, a summary and analysis are provided of the effectiveness of the mixed-methods model as used in this study.